2022
DOI: 10.3390/jtaer17010006
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Situational Influences and Social Support on Social Commerce during the COVID-19 Pandemic

Abstract: Without question, 2020 was an unprecedented period for all businesses and consumers in the world, especially for social commerce businesses. Growing online shopping during the pandemic has proliferated the appetite of social commerce websites. Drawing on the situational influences’ theory and social support theory, the purpose of this study was to investigate the impact of situational influences during the COVID-19 pandemic on online purchase intention across the big five personality traits. The data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 103 publications
(109 reference statements)
1
11
0
3
Order By: Relevance
“…This suggests that consumers may want to place an order immediately during watching interactive video advertisements on their phones, so the related function could be added in the advertisement design process. In addition, online interaction in social media can help consumers increase product involvement and purchase intention ( Bazi et al., 2022 ). In order to further increase product involvement, advertisements are suggested to introduce more relevance between the product and the audience, or integrate marketing communication by introducing social interaction features of the media.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that consumers may want to place an order immediately during watching interactive video advertisements on their phones, so the related function could be added in the advertisement design process. In addition, online interaction in social media can help consumers increase product involvement and purchase intention ( Bazi et al., 2022 ). In order to further increase product involvement, advertisements are suggested to introduce more relevance between the product and the audience, or integrate marketing communication by introducing social interaction features of the media.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study in Indonesia on impulsive buying, it was demonstrated that scarcity positively influenced the increase in impulse buying and social media was found to moderate the relationship between scarcity messages and impulsive buying [71]. Furthermore, in understanding the social commerce purchase decision, it was shown that social support was not a significant driver of social commerce purchase during the pandemic but rather situation factors (convenience, positive mood and negative mood) do [72],…”
Section: A Covid-19 Pandemic and Consumer Behaviormentioning
confidence: 97%
“…The Covid-19 pandemic also affects the increase in online interactions, because people have to keep their distance, carry out their activities at home and everything related to direct interaction is switched to online. It also drives the rapid growth of social commerce (Bazi et al 2022). Based on a survey conducted by Jakpat, social commerce is in great demand during the pandemic.…”
Section: Introductionmentioning
confidence: 99%